Juanita C. Aristizábal. Fernando Vallejo a contracorriente. Rosario: Beatriz Viterbo, 2015 - Hernández Castellanos, Camilo (2017)
Fil: Fil: Hernández Castellanos, Camilo. Universidad de los Andes; Colombia.